Electrospun PHBV nanofiber containing Tea Tree Oil: physicochemical and antimicrobial activity - dos Santos, Verônica Ribeiro; Vera, Samara Domingues; de Cena, Gabrielle Lupeti; Silva, Adrielle de Paula; Lemes, Ana Paula; da Conceição, Kátia; Tada, Dayane Batista; Borges, Alexandre Luiz Souto [UNESP]; Trichês, Eliandra de Sousa (FapUNIFESP (SciELO), 2023)
Aiming to produce an antimicrobial dressing for wound healing applications, in this work Tea Tree oil (TTO) was incorporated into PHBV nanofibers by absorption. It was observed increase in the nanofiber diameter due to 5% TTO absorption efficiency, which also led to a 54% decrease in the contact angle. The releasing assay indicates a 6.8% oil release in the first 24 h – being probably the oil deposited at the polymer surface – followed by a minimal release at 48 h. The set of antimicrobial assays performed suggests the incorporation of TTO optimized the antimicrobial activity of the polymer for E. coli and C. albicans, while against S. aureus no significant difference was observed. The MTT assay showed no cytotoxicity of PHBV, but the incubation of L929 fibroblast cells with PHBV-TTO reduced cell viability. Overall, the PHBV nanofibers containing TTO present great potential as an antimicrobial dressing.
Keywords: antimicrobial activity; nanofiber; PHBV; tea tree oil; wound healing